Assessing validity of the Klenico diagnostic software system in a large psychotherapeutic inpatient sample - Stefan Reutimann; Noah Hübscher; Noah Hübscher; Jasmin Steiner; Ulrich Voderholzer; Ulrich Voderholzer; Mareike Augsburger (Frontiers Media S.A., 2023)
IntroductionMental disorders are often underdiagnosed in routine diagnostic procedures due to the use of unstandardized assessments; this can result in people either not receiving necessary treatment or receiving ineffective treatment for their condition. Klenico is an online diagnostic software system that facilitates diagnosis of mental disorders in adults through the use of standardized procedures. The procedure encompasses two modules, self-report and clinical validation. The current study aimed to confirm the validity of the Klenico assessment in a large clinical sample.MethodsFully anonymized data from 495 adult inpatients were used. ICD-10 diagnoses were made during an initial interview by the clinical staff. Afterwards, patients filled out self-report questionnaires (BDI-II, BSI, EDE-Q, OCI-R, PHQ-D, and Y-BOCS) and completed the Klenico self-report module, which involves selecting and rating the severity of applicable symptoms. Finally, in the clinical validation module, mental health professionals validated the symptoms endorsed in the self-report module. Six Klenico domains were tested against patient self-reports and routine ICD-10 diagnoses by following the multitrait-multimethod approach. Internal consistency was assessed by calculating Cronbach's alpha.ResultsThe Klenico depressive disorders, OCD, and somatoform disorders domains revealed high correlations with the congruent questionnaires (i.e., those pertaining to these specific disorders) and revealed low correlations with the noncongruent questionnaires (i.e., those pertaining to other disorders), therefore evidencing construct validity. For the eating disorders and psychotic disorders domains, divergent validity was demonstrated. For the anxiety disorders domain, although analysis mostly indicated construct validity, this should be further confirmed.DiscussionOverall, the results largely confirmed the construct validity of the Klenico assessment, demonstrating its use as an easy-to-use, valid, standardized, and comprehensive instrument for diagnosing mental disorders.